Medical Marvels / EOS M 300-4 Sets the New Standard for Industrial 3D Printing in Medical - Davies Samuel; Griffins Laura (Bpa Worldwide, 2022)
Healthcare: The Latest in Customised Care and Devices, Emerging Markets: Spare Parts to Packaging, Business Case: What's Driving the Adoption of AM?.